Sodium Benzoate Delays the Development of Drosophila melanogaster Larvae and Alters Commensal Microbiota in Adult Flies - Dong, Yuling; Ding, Zhongfeng; Song, Linxia; Zhang, Desheng; Xie, Changjian; Zhang, Shujing; Feng, Ling; Liu, Hongliang; Pang, Qiuxiang (Frontiers in Microbiology, 2022)
Sodium benzoate (SB), the sodium salt of benzoic acid, is widely used as a preservative in foods and drinks. The toxicity of SB to the human body attracted people’s attention due to the excessive use of preservatives and the increased consumption of processed and fast foods in modern society. The SB can inhibit the growth of bacteria, fungi and yeast. However, little is known of the effect of SB on host commensal microbial community compositions and their functions. Here, we investigated the effect of SB on the growth and development of D. melanogaster larvae and whether SB affects the commensal microbial compositions and functions. We also attempted to clarify the interaction between SB, commensal microbiota and host development by detecting the response of commensal microbiota after the intervention. The results show that SB significantly retarded the development of D. melanogaster larvae, shortened the lifespan and changed the commensal microbial community. In addition, SB changed the transcription level of endocrine coding genes such as ERR and DmJHAMT. These results indicate that the slow down in D. melanogaster larvae developmental timing and shortened lifespan of adult flies caused by SB intake may result from the changes in endocrine hormone levels and commensal microbiota. This study provided experimental data that indicate SB could affect host growth and development of D. melanogaster through altering endocrine hormone levels and commensal microbial composition.